The Implementation Of Problem Based Learning Model Suported By Audio Visual Media To Enhance Student Learning Activities - Hanim, Nafisah; Eriawati, Eriawati; Elita, Elita Agustina; Rahmadani Putri, Riri; Ratna Putri, Cut; Putri, Ghaifira Husna (Universitas Islam Negeri Ar-Raniry, 2026)
Low student learning activity in class VII MTsN 2 Banda Aceh on the respiratory system material was marked by minimal student participation in asking questions, discussing, and expressing opinions during the learning process. This condition indicates the need to apply innovative and student-centered learning models and media. This study aims to improve student learning activities through the application of the Problem-Based Learning (PBL) model assisted by audio-visual media. This study uses a Classroom Action Research (CAR) design carried out in two cycles, each covering the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of 37 seventh-grade students at MTsN 2 Banda Aceh. Data were collected using a learning activity observation sheet covering six indicators, namely visual, oral, listening, writing, mental, and emotional activities. The results showed that the average student learning activity increased from 79% in cycle I, which was categorized as high, to 91% in cycle II, which was categorized as very high. The increase occurred consistently across all learning activity indicators. Thus, the application of the PBL model assisted by audio-visual media proved to be effective in increasing student learning activities in biology learning. Keywords: Learning Activities; Problem-Based Learning; Audio-Visual Media; PTK.